(3GdQhVI GdWHjIs - (3CHhSYjO YHjOGddg Hf LHQFjd Hf YHjOGddg Hf HNJjThYs; (3GHf HNJjThY , YHjOGddg Hf LHQFjd Hf YHjOGddg, CHh SYjO,J (B453 (3g` s ((3jhMfG Hf bSjS OGfjGd GdcdOGfj s)
(3ChdgG (B:s
(3Gddge CYf Ydi WGYJc cd aGVd CWGd GdHbGA GdCSJGP SCdfi COGe Gddg JCjjOg Cf GNJUQ dg ef cJGHj GdefYhJ HJPcQI GdMGVQ hRGO GdeSGaQ s
(3BNQgG (B:s
(3GdUhJ gh bQY LSe oeYJOd aj GdUdGHI hGddjf ddghi, hojecf ajg GdRjGOI hdofbUGf hGdJbWjY hGdEJUGd hCf bQY GdCLSGe GdUdHI dGjecf ajg Je GdcJGH s
(3fSNI KGfjIs
(3hGdfSNI ebGHdI hocJHJ SfI (B1746(3es
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B192 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B238s
Keywords: (3GdWHs